Impact of Farmer Producer Organizations on Price and Poverty Alleviation of Smallholder Dry Chillies Farmers in India - Kumar, K. Nirmal Ravi; Reddy, M. Jagan Mohan; Shafiwu, Adinan Bahahudeen; Reddy, A. Amarender (Research on World Agricultural Economy, 2023)
This study investigates the impact of Farmer Producer Organizations (FPOs) on smallholder dry chilli farmers in Guntur district, Andhra Pradesh, with a focus on price realization and poverty alleviation. Two specific FPOs, Red Chilli Farmer Producer Organisation and Spoorthi Chilli Producers Company Ltd., from the Guntur district of Andhra Pradesh were chosen for the study based on their substantial business turnover and comprehensive backward and forward linkages to their farmer-members. The smallholder farmers were stratified into two groups viz., treated (161) and untreated (n = 315) based on the FPO membership criterion. The Foster-Greer-Thorbecke model revealed that the poverty incidence among untreated farmers was recorded at 0.691, which was approximately 49 percent higher than the poverty incidence of treated farmers (0.352). The depth and severity of poverty were also greater among untreated farmers, with a poverty depth of 0.494 compared to the lower value of 0.126 observed among treated farmers. The results from Endogenous Switching Regression Model revealed a significant positive relationship between FPO membership and both price realization and poverty alleviation. Farmers with FPO membership experienced 2.11 percent higher prices and 39.14 percent higher annual agricultural income compared to untreated. Factors such as education, adherence to Good Agricultural Practices, farm experience, access to improved inputs, and credit significantly influenced FPO membership. The study concludes that FPO membership plays a crucial role in improving the standard of living for smallholder dry chilli farmers by increasing prices and income. So, this research sheds light on the significance of FPOs in enhancing the economic well-being of smallholder dry chilli farmers in Andhra Pradesh.